High variability in toxicity of welding fume nanoparticles from stainless steel in lung cells and reporter cell lines: the role of particle reactivity and solubility. Issue 10 (26th November 2019) - McCarrick, Sarah; Wei, Zheng; Moelijker, Nynke; Derr, Remco; Persson, Kjell-Arne; Hendriks, Giel; Odnevall Wallinder, Inger; Hedberg, Yolanda; Karlsson, Hanna L.
Abstract: Millions of people in the world perform welding as their primary occupation resulting in exposure to metal-containing nanoparticles in the fumes generated. Even though health effects including airway diseases are well-known, there is currently a lack of studies investigating how different welding set-ups and conditions affect the toxicity of generated nanoparticles of the welding fume. The aim of this study was to investigate the toxicity of nine types of welding fume particles generated via active gas shielded metal arc welding (GMAW) of chromium-containing stainless steel under different conditions and, furthermore, to correlate the toxicity to the particle characteristics. Toxicological endpoints investigated were generation of reactive oxygen species (ROS), cytotoxicity, genotoxicity and activation of ToxTracker reporter cell lines. The results clearly underline that the choice of filler material has a large influence on the toxic potential. Fume particles generated by welding with the tested flux-cored wire (FCW) were found to be more cytotoxic compared to particles generated by welding with solid wire or metal-cored wire (MCW). FCW fume particles were also the most potent in causing ROS and DNA damage and they furthermore activated reporters related to DNA double- strand breaks and p53 signaling. Interestingly, the FCW fume particles were the most soluble in PBS, releasing more chromium in the hexavalent form and manganese compared to the other fumes. These results emphasize the importance of solubility of different metal constituents of the fume particles, rather than the total metal content, for their acute toxic potential.